Upaya Meningkatkan Hasil Belajar Siswa Melalui Pembelajaran Konsep Keliling dan Luas Persegi Panjang Menggunakan Media Benda Konkret di Kelas VII SMP Muhammadiyah 4 Palembang - Muslimin, Muslimin (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2021)
The learning outcomes of class VII students of SMP Muhammadiyah 4 Palembang on the subject of circumference and area of flat shapes are still relatively low. This is because the learning carried out by educators is only focused on existing learning resources without using media that can help students understand the concept of perimeter and area of a rectangle so that students easily forget and find it difficult to complete the application of these concepts. Therefore, it is necessary to conduct research on the application of learning that is able to improve learning outcomes and understanding of concepts for students. One solution to this problem is to apply the learning of the concept of perimeter and area of a rectangle through the media of concrete objects. From the results of this study, it was concluded that learning the concept of perimeter and area of a rectangle through the media of concrete objects could improve the learning outcomes of seventh grade students of SMP Muhammadiyah 4 Palembang.